THE BRICS ERA: INDONESIA’S PATH TO SUSTAINABLE TRADE LAW AND DEVELOPMENT: (Balancing Growth, Sustainability, and Rights in Trade) - Inaya Yuniar, Maulina (Jurnal Paradigma Hukum Pembangunan, 2025)
Indonesia’s decision to join BRICS signifies a major shift in its economic and geopolitical strategy, offering new trade opportunities, financial access, and diplomatic leverage among emerging economies. This study examines the benefits and challenges of Indonesia’s BRICS membership, focusing on trade relations, environmental sustainability, and labor rights. The research problem lies in how Indonesia can maximize BRICS advantages while mitigating economic and regulatory risks. Using a qualitative approach, this paper analyzes policy reports, trade data, and expert opinions to assess BRICS’s impact on Indonesia’s economy and governance. Results indicate that BRICS provides expanded market access and financing through the New Development Bank, yet challenges arise in balancing regional commitments, sustainable resource management, and labor protection. The study concludes that Indonesia must adopt a strategic approach by maintaining ASEAN and Western ties, fostering economic diversification, and implementing fair trade policies to optimize BRICS’ benefits while addressing potential drawbacks.